How Late-Life Working Affects Depression Among Retirement-Aged Workers? An Examination of the Influence Paths of Job-Related (Non–Job-Related) Physical Activity and Social Contact. Issue 8 (11th August 2022) - Li, Jiannan; Yuan, Bocong; Lan, Junbang; Huang, Xinting
Abstract : Delayed retirement can imply both bright and dark sides for mental health of older workers, as it facilitates the job demand physical activity and social contact, while dampens the non-job demand physical activity. The overall impact of delayed retirement on mental health depends on which mediation path is dominant. Thus, policymakers should improve the policy design in order to better protect the health of older workers. Abstract : Purpose: This study investigates the influence paths that late career participation affects depression of older workers. Method: The data of China Health and Retirement Longitudinal Study (2018) are used. Those who have reached the statutory retirement age in China (>60 years for males/>55 years for females) are investigated. Results: Late career participation may positively affect job-related physical activity and social contact (2.110 and 0.028, P < 0.01) and negatively affect non–job-related physical activity (−0.343, P < 0.01). Besides, job-related physical activity may exacerbate depression symptoms among older workers (0.017, P < 0.01), whereas non–job-related physical activity and social contact may alleviate it (−0.015 and −0.038, P < 0.01). Conclusions: Late career participation could be associated with depression through different pathways involving job-related (and non–job-related) physical activity and social contact. The overall impact of late career participation on depression would depend on which influence pathway is dominant.